Milk Tofu Onde Quality - Ningsih, Dwi (ANIMAL PRODUCTION, 2002)
The study on âThe Quality of Milk Tofu Ondeâ observed from its crispiness,colour,taste and texture was conducted to socialise the product of milk. Onde is a kind of snack which is popular in Indonesia and it easy to produce with simple eguipment. As much as 562.5 gs fresh milk tofu, 562.5 gs wither milk tofu and 1500 gs of wheat flour for the purpose of study. Data on crispiness, colour, taste and texture of milk tofu ande expressed in score, were obtained through 20 panelists and was analized with Randomized Group Design followed by an orthogonal polynomial teast. The first factors were sort of tofu (T) e.i fresh milk tofu and wither milk tofu. The second factors were level of tofu (S) e.i 50 percent, 75 percent and 100 percent of wheat flour or their proportion (g) were (125:125); (187.5:62.5); (100:0). The study showed that milk tofu onde from wither milk more crispy significantly (P>0.01) than those from fresh milk. Â The level of tofu gave a significant effect (P>0.01) on crispiness. This was shown byÂ  a quadrater Â regression of : Y1 = c9.0712Â  + 0.5093X cÂ  0.0030X2 and Y2 = c3.3865 + 0.4949X c 0.0033X2 for fresh milk tofu and wither milk tofu respectively. Milk tofu onde from wither milk more brownnes significantly (P>0.01) than those fron fresh milk. The level of Â tofu gave a significant effect (P>0.01) on colour. This was shown by a linier regression of Y1 = 8.4244 + 4.4625x and Y2 = 8.7734 Â + 10.0745X for fresh milk tofu and wither milkÂ  tofu respectively. Milk tofu onde from wither milk more delicious significantly (P>0.01) than those from fresh milk. The level of tofu gave a significant effect (P>0.01) on taste. This was shown by a linier regressions of Y1 = 8.3383 + 0.0422 X and by a quadrater regression of Y2 = 3.5200 + 0.5156 X â 0.0033 X2 for fresh milk tofu and wither milk tofu respectively. Texture of milk tofu onde from fresh milk more dense significantly (P>0.01) than tose from wither milk. The level of tofu gave a significant effect (P>0.01) on texture. This was shown by a linier regressions of Y1= 5.4150 + 11.9630 X and Y2= 10.7880 + 1.5633 X for fresh milk tofu and wither milk tofu respectively. The study indicated that milk tofu onde from wither milk being more crispy, brownness, delicious and denseless texture than those from fresh milk. The best level of milk tofu was 75% on daugh. (Animal Production 4(1): 11-20 (2002)Key words : âMilk tofu ondeâ, crispiness